Didática multissensorial e o ensino inclusivo de ciências - Anjos, Paola Trama Alves dos [UNESP]; Camargo, Eder Pires de [UNESP] (My University, 2011)
Considering the discussions about the inclusion of disabled people in the regular education and the need to find methodologies that meet the diverse needs of students, this work brings to the discussion the multisensory didactic perspective as an alternative to science inclusive teaching.

Considerando as discussões sobre a inclusão das pessoas com deficiência no ensino regular e a necessidade de encontrar metodologias que atendam as diferentes necessidades dos alunos, este trabalho traz para a discussão a perspectiva da Didática Multissensorial como alternativa para um ensino inclusivo de Ciências.
Multisensory didactic and science inclusive teaching
Keywords: Educacional inclusion; Multisensory didactic; Science teaching; Inclusão educacional; Didática multissensorial; Ensino de ciências